Nesquehonite sequesters transition metals and CO2 during accelerated carbon mineralisation. (December 2016) - Hamilton, Jessica L.; Wilson, Siobhan A.; Morgan, Bree; Turvey, Connor C.; Paterson, David J.; MacRae, Colin; McCutcheon, Jenine; Southam, Gordon
Graphical abstract: Highlights: Nesquehonite rapidly and effectively sequesters Cr, Mn, Co, Ni and Cu from solution. Trace metal uptake appears to occur by substitution for Mg 2+ in nesquehonite. Trace metals are retained during recrystallisation of nesquehonite to form large crystals. Fe-oxyhydroxides also sequester trace metals, indicating multiple uptake pathways. The environmental risk of trace metal release from carbon mineralisation is low. Abstract: Acid leaching of ultramafic rocks to produce Mg 2+ - and Ca 2+ -rich solutions for mineral carbonation may inadvertently leach toxic trace metals. This study investigates the capacity of nesquehonite (MgCO3 ·3H2 O), a common product of mineral carbonation at Earth's surface conditions, to sorb Cr, Ni, Mn, Co and Cu from solution. Our results demonstrate that upon precipitation, nesquehonite rapidly sequesters transition metals present in solution at concentrations from 10 to 100 mg/L. Trace metal uptake appears to occur by substitution for Mg 2+ in the nesquehonite crystal structure, and also by incorporation into minor, metal-rich phases, such as Fe-oxyhydroxides. This indicates that first row transition metals will likely be trapped and stored within Mg-carbonate minerals produced in industrial mineral carbonation reactors and in landscapes modified to capture atmospheric CO2 via enhanced weathering. Thus, it is unlikely that trace metals will pose an environmental risk in the event of accidental release of wastewater.